On the First Calculations of National Income in the Interwar Lithuania and Albinas Rimka’s Errors, Which Did Accelerate the Fall of Democracy - Norkus, Zenonas (Lietuvos istorijos studijos, 2017)
The contemporary system of the national accounts (SNA) framework is used to re-analyse the pioneering calculation of the national income of Lithuania in 1924, which Albinas Rimka (1886–1944) published in 1926 as part of his preparations to take the office of Minister of Finance in the Left-of-the-Centre Peasant Populist and Social-Democratic parties coalition government. This government ruled Lithuania in June-December 1926, after the Christian Democrats defeat in the May 1926 election to the III Diet of the Republic of Lithuania. The “brutto national profit”, measured by A. Rimka, corresponds to net national income (NNI) in the sense of the SNA. His estimate has a downward bias, because Rimka applied an excessive fixed capital depreciation rate to derive NNI from the gross national income (GNI) and did not include the value of the non-commercial public sector services (public goods) into GNI and NNI. The ultimate proof of the underestimation was the following: the NNI per capita (582 Litas), according to Rimka, is lower than the yearly subsistence minimum (633 LTL), according the consumption norms calculated by the Lithuanian Central Statistical Bureau for 1924. According to the author’s minimal estimate, the NNI per capita was 748 LTL per capita, while GNI was 815 LTL per capita. In underestimating the real size of the Lithuanian economy, A. Rimka considered the taxation overload as the main issue and the new government proclaimed the budget cuts as the priority of its economic policy. It was implemented in the budget project prepared by A. Rimka for 1927. Among others, the austerity policies had to hit two powerful interest groups: the clergy, represented by the Christian Democrats, and the military officership, where a small Nationalist party had many sympathisers. Encouraged and supported by the Christian Democrats, the military staged a coup on 17 December 1926, ending the short period of parliamentary democracy in Lithuania (1920–1926). Typically, authoritarian coups in underdeveloped countries are provoked by the populist economic policies of the Leftist governments, causing inflation by government overspending to placate under-privileged social groups. The authoritarian coup in Lithuania in 1926 is a deviating case of democracy, undermined by the austerity policies of the Leftist government, caused (jointly with other causal conditions) by the mistakes in the macroeconomic measurements.
Keywords: national income of Lithuania; national accounting; Albinas Rimka; austerity; the fall of democracy in Lithuania in 1926